A Challenging Case of Simple Limbal Epithelial Transplantation (SLET) in Limbal Stem Cell Deficiency Following Chemical Injury: A Case Report: Poster Presentation - Case Report - Resident - Amanda, Lia; Widyawati, Syska; Martha, Faraby; Zarwan, Jessica (Majalah Oftalmologi Indonesia, 2023)
Introduction : Limbal stem cell deficiency (LSCD) often arises following trauma or inflammation that hinders corneal epithelium healing, commonly caused by chemical or thermal injuries. Despite significant advancements, treating LSCD remains challenging. This case highlights a challenging case of simple limbal epithelial transplantation (SLET) in LSCD following chemical injury. Case Illustration : A 20-year-old male presented with reduced vision in left eye following an alkaline chemical injury (grade III) was diagnosed with unilateral LSCD. Upon examination, conjunctivalization of the peripheral cornea, a central corneal cicatrix, and stromal neovascularization present after previous necrotomy, tenoplasty, and amniotic membrane transplantation (AMT). The patient then underwent SLET, with limbal biopsies from the collateral eye. Four months after surgery the visual acuity improved from 3/60 to 6/15 with spectacles. However, the cornea conjunctivalization still developed despite improved visual acuity. Discussion : To effectively manage the recurrence of stem cell deficiency, other stem cell transplantation techniques are needed to manage the problem. Combining different limbal stem cell transplantation approaches can be customised to address the problem and achieve lasting results. Conclusion : Prompt diagnosis and treatment of LSCD is crucial to prevent complications and blindness. SLET is a surgical option for LSCD after chemical injury, but this report highlights a challenging case and the need for the alternatives approaches.